DIVERSITY AND ABUNDANCE OF MACROZOOBENTHOS IN THE WATERS OF KELAGIAN LUNIK ISLAND PADANG CERMIN DISTRICT PESAWARAN REGENCY - Wahyu Hari Nugroho; Henni Wijayanti Maharani; Suparmono Suparmono (AQUASAINS, 2021)
Kelagian Lunik Island is located in Pesawaran Regency which has three ecosystems that are mangrove, seagrass, and beaches ecosystems. These three ecosystems affect the survival of one of the biotas living on the substrate of the water that is macrozoobenthos. Macrozoobenthos are invertebrate biota that live on the base of the substrate or inside the substrate. The role that is large enough in the aquatic ecosystem is to describe the organic matter that falls to the water base. It is therefore the research to study the diversity and abundance of macrozoobenthos. This research was conducted in December 2019 to January 2020 located on Kelagian Lunik Island, Padang Cermin District, Pesawaran Regency, Lampung Province. The method is purposive sampling at five stations with three repetitions. The results show that the highest abundance found in the species Tellina perna with 2880 ind/m3 on Station 1, Nassarius globosus with 1851 ind/m3 on station 2, and Marshalora adversa with 1645 ind/m3, 2674 ind/m3, and 1851 ind/m3 at stations 3, 4 and 5. The biodiversity of macrozoobenthos such as the index of diversity and uniformity in the waters of Kelagian Lunik Island is relatively high and the dominant index is relatively low thereby the condition of the water can fit in the good category.